2007
DOI: 10.3892/ijo.31.4.793
|View full text |Cite
|
Sign up to set email alerts
|

Low level STK15 amplification in histologically benign urothelium of patients with bladder cancer adversely predicts patient outcome following cystectomy

Abstract: Abstract. The aim of this study was to investigate STK15 amplification in histologically benign urothelium and invasive tumor tissue of urothelial bladder cancer patients in relation to clinicopathologic and molecular characteristics, and to analyze a hypothesized association between the STK15 single nucleotide polymorphism at site T91A (Phe31Ile) and STK15 gene amplification. A tissue microarray (TMA) was constructed and contained formalin-fixed paraffin-embedded tumor tissue and matching histologically benig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Our data showed that overexpressed Aurora-A protein in most HNSCC tumor tissues was primarily distributed in the cytoplasm compared to that found in nucleus of tumor (~10-15%) and the adjacent non-tumor tissues (~5-10%). Similar finding also observed in other human cancer tissues, such as bladder, colorectal and ESCC[5, 43, 44]. In contrast to these studies, several reports indicated that Aurora-A accumulated in the nucleus and associated with advanced cancer stage[1, 37].…”
Section: Discussionsupporting
confidence: 81%
“…Our data showed that overexpressed Aurora-A protein in most HNSCC tumor tissues was primarily distributed in the cytoplasm compared to that found in nucleus of tumor (~10-15%) and the adjacent non-tumor tissues (~5-10%). Similar finding also observed in other human cancer tissues, such as bladder, colorectal and ESCC[5, 43, 44]. In contrast to these studies, several reports indicated that Aurora-A accumulated in the nucleus and associated with advanced cancer stage[1, 37].…”
Section: Discussionsupporting
confidence: 81%
“…Allelic variation in AURKA has been associated with AURKA expression levels and increased risk of multiple cancers in a meta-analysis of 9,549 cases (Ewart-Toland et al 2005; Matarasso et al 2007). AURKA amplification is very prevalent in bladder tumors (64%) and tumor AURKA gene and protein expression levels are associated with tumor recurrence and shorter survival time (Comperat et al 2007; Denzinger et al 2007; Schultz et al 2007). The previously examined AURKA polymorphism T91A was not associated with bladder cancer prognosis in a study of 135 patients (Schultz et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The significant advantage of FISH (i.e., the use of fluorophore‐labeled probes) over ISH (i.e., the use of chromogenic labeled probes) is the ability to apply and visualize more than two probes simultaneously, which results in a multi‐color (i.e., multi‐marker) hybridization (mFISH). In this way, multiple regions located on the same chromosomes or on different chromosomes can be addressed and analyzed at the same time (Denzinger et al., 2007; Miyake et al., 2023; Pothos et al., 2008; Schwarz et al., 2004; Schwarz et al., 2008). Additionally, individual markers can be visualized and assessed separately or simultaneously by using microscopic single‐color or dual‐ or even three‐color filters.…”
Section: Introductionmentioning
confidence: 99%